Community Orientation Scale among Community Health Nurses in Fiji: Scale development and psychometric evaluation - Sachiko Tanabe; Satoko Yanagisawa; Silina Waqa Ledua; Mereani Tukana (Wiley, 2020)
Abstract Aim To develop and evaluate the reliability and validity of the COSCHN, a scale that aims to measure community orientation among community health nurses in Fiji. Design Descriptive cross‐sectional design. Methods A self‐administered questionnaire that included the 51 items in the preliminary COSCHN was distributed to community health nurses in Fiji from April-July 2016. Results Exploratory factor analysis of 226 responses (77.4% response rate) to the COSCHN revealed 30 items loading on four factors: Community Initiative Promotion, Consensus Building for Community Needs and Activity Goal, Commitment towards Work and Community Members and Mutually Trusting Relationships with Community Members towards Empowerment. Confirmatory factor analysis with high‐order factor modelling revealed a reasonable fit to the data. Cronbach's α values for the COSCHN and the four factors ranged from 0.78-0.94. Weak correlations were noted for concurrent validity, while known‐groups validity and time stability were generally satisfactory.